High-affinity RNA Aptamers Against the HIV-1 Protease Inhibit Both In Vitro Protease Activity and Late Events of Viral Replication - Sonald Duclair; Archana Gautam; Andrew Ellington; Vinayaka R Prasad (Elsevier, 2015)
HIV-1 aspartyl protease (PR) plays a key role in virion morphogenesis, underscoring the effectiveness of protease inhibitors (PI). Despite their utility, side effects and drug-resistance remains a problem. We report the development of RNA aptamers as inhibitors of HIV-1 PR for potential use in anti-HIV gene therapy. Employing Systematic Evolution of Ligands by Exponential Enrichment (SELEX), we isolated four unique families of anti-HIV-1 PR RNA aptamers displaying moderate binding affinities (Kd = 92-140 nmol/l) and anti-PR inhibitory activity (Kis = 138-647 nmol/l). Second-generation RNA aptamers selected from partially randomized pools based on two of the aptamer sequences displayed striking enhancements in binding (Kds = 2-22 nmol/l) and inhibition (Kis = 31-49 nmol/l). The aptamers were specific in that they did not bind either the related HIV-2 protease, or the cellular aspartyl protease, Cathepsin D. Site-directed mutagenesis of a second-generation aptamer to probe the predicted secondary structure indicated that the stem-loops SL2 and SL3 and the stem P1 were essential for binding and that only the 3'-most 17 nucleotides were dispensable. Anti-PR aptamers inhibited HIV replication in vitro and the degree of inhibition was higher for second-generation aptamers with greater affinity and the inhibition was abrogated for a nonbinding aptamer variant.